Carbon cloth stimulates direct interspecies electron transfer in syntrophic co-cultures - Chen, Shanshan; Rotaru, Amelia-Elena; Liu, Fanghua; Philips, Jo; Woodard, Trevor L.; Nevin, Kelly P.; Lovley, Derek R. (Bioresource technology, 2014)
This study investigated the possibility that the electrical conductivity of carbon cloth accelerates direct interspecies electron transfer (DIET) in co-cultures. Carbon cloth accelerated metabolism of DIET co-cultures (Geobacter metallireducens-Geobacter sulfurreducens and G.metallireducens-Methanosarcina barkeri) but did not promote metabolism of co-cultures performing interspecies H2 transfer (Desulfovibrio vulgaris-G.sulfurreducens). On the other hand, DIET co-cultures were not stimulated by poorly conductive cotton cloth. Mutant strains lacking electrically conductive pili, or pili-associated cytochromes participated in DIET only in the presence of carbon cloth. In co-cultures promoted by carbon cloth, cells were primarily associated with the cloth although the syntrophic partners were too far apart for cell-to-cell biological electrical connections to be feasible. Carbon cloth seemingly mediated interspecies electron transfer between the distant syntrophic partners. These results suggest that the ability of carbon cloth to accelerate DIET should be considered in anaerobic digester designs that incorporate carbon cloth.